DAUPHINÉ TWINNING AND TEXTURE MEMORY IN POLYCRYSTALLINE QUARTZ. PART 1: EXPERIMENTAL DEFORMATION OF NOVACULITE - Wenk H.-R.; Lonardelli I.; Rybacki E.; Dresen G.; Barton N.; Franz H.; Gonzalez G. (My University, 2006)
Mechanical Dauphiné twinning in quartz has been of long-standing interest, both in single crystals and polycrystalline aggregates. This study investigates texture development in fine-grained quartz rock novaculite with no initial texture using compression experiments conducted in the Paterson gas apparatus to explore the influence of stress and temperature. Texture patterns are measured with time-of-flight neutron diffraction and hard synchrotron X-rays, analyzing diffraction data with the Rietveld method. Similar texture patterns are observed as described previously but the new results establish a profound influence of temperature and document that twinning initiates at stresses less than 50 MPa. Possibilities of using Dauphiné twinning as a paleopiezometer in quartz-bearing rocks are discussed. © Springer-Verlag 2006.
Keywords: DEFORMATION EXPERIMENTS; QUARTZ; SYNCHROTRON X-RAYS; TEXTURE; TWINNING